Comparison of Different Carriers to Maintain a Stable Partial Nitrification Process for Low-Strength Wastewater Treatment - Zhang, Kuo; Li, Xinjue; Ni, Shou-Qing; Liu, Sitong (Frontiers in Bioengineering and Biotechnology, 2022)
Practical application of the partial nitritation-anammox process has attracted increasing attention due to its low operational costs. However, ammonia-oxidizing bacteria (AOB) are sensitive to the ammonia loading rate and DO concentration, limiting their potential for application in mainstream wastewater treatment. In order to improve the environmental adaptation of AOB, five 18 L sequencing batch reactors were operated in parallel at room temperature (22 ±4℃) to explore the nitritation performance with different carrier materials, including sepiolite-non-woven carrier (R1), zeolite-non-woven carrier (R2), brucite-non-woven carrier (R3), polyurethane carrier (R4) and non-woven carrier (R5). The ammonia oxidation rate (AOR) in R1 reached the highest level of 0.174 g-N·L-1·d-1 in phase II, which was 1.4-fold higher than the control reactor (R4). To guarantee a stable supply of nitrite for anammox process, the nitrite accumulation efficiency (NAE) was always higher than 77 % even though the free ammonia (FA) decreases to 0.08 mg-N/L and the pH decrease to 6.8±0.3. In phase V, the AOR in R1 reached 0.206 g-N·L-1·d-1 after the dissolved oxygen (DO) content increase from 0.7±0.3 mg/L to 1.7±0.3 mg/L. The NAE in R1 was consistently higher than 68.6%, which was much higher than the other reactor systems (R2-43.8%, R3-46.6%, R4-23.7%, R5-22.7%). Analysis of 16S rRNA gene sequencing revealed that the relative abundance of Nitrobacter and Nitrospira in R1 was significantly lower than other reactors, indicating that the sepiolite carrier plays an important role in the inhibition of nitrite oxidizing bacteria. These results indicate that the sepiolite non-woven composite carrier can effectively improve the nitritation process, which is highly beneficial for the application of partial nitritation-anammox for mainstream wastewater treatment.